2016
DOI: 10.18203/2394-6040.ijcmph20164268
|View full text |Cite
|
Sign up to set email alerts
|

Application of latent class analysis to estimate susceptibility to adverse health outcomes based on several risk factors

Abstract: Background: The study demonstrates the use of latent class analysis (LCA) to segregate population in two latent classes e.g. susceptible or not susceptible to adverse health outcomes according to the observed risk factors as a method of medical diagnosis. Methods: The present study uses a secondary data set on 420 patients referred to the University of California, Los Angeles (UCLA). Adult Cardiac Imaging and Hemodynamics Laboratories for Dobutamine stress echocardiography (DSE) between March1991 & March1996. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In a study by Dey et al (2016), based on seven observed risk factors, LCA was used to classify individuals into two latent classes 'susceptible to adverse health outcomes groups' and 'not susceptible to adverse health outcomes groups'. 39 Another study in China applied LCA to 10 observed complications and comorbidities of patients with type 2 diabetes and categorised the individuals into four latent classes, namely 'complications and comorbidity groups', 'high risk of complications group', 'high risk of comorbidities and Cardiovascular Disease groups' and 'diabetes without complications and comorbidities group'. 40 A study in West Azerbaijan province among the patients with hypertension aged 50 years and above used four indicators, such as dietary patterns, physical activity, tobacco use and high BP control to categorise the patients with hypertension into three latent classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Dey et al (2016), based on seven observed risk factors, LCA was used to classify individuals into two latent classes 'susceptible to adverse health outcomes groups' and 'not susceptible to adverse health outcomes groups'. 39 Another study in China applied LCA to 10 observed complications and comorbidities of patients with type 2 diabetes and categorised the individuals into four latent classes, namely 'complications and comorbidity groups', 'high risk of complications group', 'high risk of comorbidities and Cardiovascular Disease groups' and 'diabetes without complications and comorbidities group'. 40 A study in West Azerbaijan province among the patients with hypertension aged 50 years and above used four indicators, such as dietary patterns, physical activity, tobacco use and high BP control to categorise the patients with hypertension into three latent classes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have adopted the LCA approach to identify risk factors clustering within the heterogeneous population. In a study by Dey et al (2016), based on seven observed risk factors, LCA was used to classify individuals into two latent classes ‘susceptible to adverse health outcomes groups’ and ‘not susceptible to adverse health outcomes groups’ 39. Another study in China applied LCA to 10 observed complications and comorbidities of patients with type 2 diabetes and categorised the individuals into four latent classes, namely ‘complications and comorbidity groups’, ‘high risk of complications group’, ‘high risk of comorbidities and Cardiovascular Disease groups’ and ‘diabetes without complications and comorbidities group’ 40.…”
Section: Methodsmentioning
confidence: 99%
“…Dey et al proposed a latent class model for identifying subgroups according to health effects in a large population. It used LCA to produce a clustering of patients [12] by using random sampling without replacement, assuming local independence between observed variables, and each patient is assigned to one class where Bayesian Information Criteria is used to select the best number of classes in the model.…”
Section: A Latent Class Analysis: a Brief Overviewmentioning
confidence: 99%
“…However, factors that are associated with unknown adverse events (AEs) following mRNA COVID-19 vaccination, such as age, gender, and existing diseases or high-risk subgroups, have not been well established [ 9 11 ]. The identification of patterns and factors can provide insights into preventive measures and management strategies concerning unknown AEFIs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to (1) identify the patterns of serious AEFI profiles after COVID-19 vaccination within the VigiBase, the World Health Organization (WHO)’s international database of suspected adverse drug reactions, and (2) describe potential factors to identify subgroups in mRNA COVID-19 vaccine reports with similar serious AEFI profiles. To achieve these aims, we applied latent class analysis (LCA), a statistical method used to identify the relationships among a set of unobserved dichotomous or polytomous variables that can be viewed as indicators [ 12 ]. This study was conducted in accordance with the Helsinki Declaration.…”
Section: Introductionmentioning
confidence: 99%